Uji Kinerja Mesin Pencacah Plastik (Studi Kasus Bank Sampah Tasikmalaya (BST) di Kecamatan Singaparna, Kabupaten Tasikmalaya) - wahyu kristian sugandi; Asep Yusuf; Totok Herwanto; Sidik Maulana (The University of Lampung, 2018)
ABSTRACTGarbage is solid waste, consisting of organic and inorganic substances or materials that are considered to have no longer beneficial and must be managed properly so as not to endanger the environment. Garbage has been a complicated problem especially in big cities. Singaparna, Tasikmalaya has been produced 154.72 m3 of plastic waste every day. Plastic waste collected by BST is only sort and sold at low prices to the city. To increase the sale value, the plastic waste needs to be chopped in advance. Therefore, the Laboratory of Agricultural Equipment and Machinery FTIP Unpad had developed a plastic waste counting machine to be applied to the community, especially in BST to produce the desired plastic count. However, this machine not yet performance testing data, so it needs to do research regarding performance tests. The purpose of this study is to examine the performance of the plastic counter machine which includes measuring the capacity of the machine, calculating the rendering yield, calculating the length of the enumeration measuring the engine noise level and measuring the engine vibration level. The research method used had descriptive analysis method, it was measuring and calculating the structural components and engine performance. The results of the study in measuring the performance test showed that the actual capacity of the machine was 19.18 kg / hour, the enumeration chopper was 84%, the percentage of plastic chopping length was 86.89%, the noise level was 104.77dB, and the engine vibration was 18.3 mm / s. Key Note : plastic chopper, performance test, tasikmalaya garbage bank